Dividend Payment and its Impact on the Value of Firms Listed on Istanbul Stock Exchange: A Residual Income Approach - Budagaga, Akram (International Journal of Economics and Financial Issues, 2017)
The aim of this study is to examine the impact of dividend payments on the value of firms listed on the Istanbul Stock Exchange (ISE). The study has been adapted the Residual Income Approach based on Ohlson’s (1995) valuation model. By testing different statistical techniques, fixed effect is applied on panel data for 44 firms listed on Istanbul Stock Exchange for the period 2007-2015, inclusive. The findings show a positive significant relationship between dividend payments and the value of firms. The results tend to support agency cost rather than the signaling hypothesis explanation. Moreover, the study suggests that the dividends irrelevance hypothesis is invalid in the case of firms listed on the (ISE). Keywords: dividend payment, residual income, value of firms. JEL Classifications: C58, E44